Molecular cloning and characterization of a cDNA encoding a polyketide synthase from Melastoma decemfidum - Jamalnasir, Hidayah; Wagiran, Alina; Shaharuddin, Noor Azmi; Abd Samad, Azman (Versita, 2014)
A famous plant polyketide synthase (PKS) is a chalcone synthase (CHS), which catalyzes the formation of naringenin chalcone, a limiting factor for flavonoid biosynthesis. Flavonoids such as naringenin and kaempferol-3-O-(2″,6″-di-O-p-trans-coumaroyl glucoside) have been identified from the flower extracts of Melastoma decemfidum RoxB. Therefore, a study was conducted to clone and characterize the pks gene from M. decemfidum. A newly isolated full-length cDNA containing the pks sequence (designated MdCHS; GenBank accession No. KF234569) was found to harbour a 1,355-bp open reading frame encoding 392 amino acids. The deduced MdCHS protein, which had a predicted molecular weight of approximately 42.6 kDa, exhibited 89% sequence identity to CHS from Anthurium andraeanum (GenBank accession No. AY232492) and 91% to those from Camellia sinensis (D26594) and Camellia chekiangoleosa (ADW11243). Southern blot analysis indicated that at least five pks genes are present in M. decemfidum. Additionally, transcription analysis revealed that pks gene expression was higher in roots than in other tissues (shoots, leaves, stems, flower buds and flowers). In conclusion, the characterization and cloning of the MdCHS gene further elucidates its role in flavonoid biosynthesis.